The Symbolic Meaning of Ready to Tetek In The Wedding Custom of Dayak Bakati Kanayatn Setango Ethnicity in Binua Tambang Laut Tebas District Sambas Regency - Ledy Rivena; Yohanes Bahari; Riama Al Hidayah; Fatmawati Fatmawati (International Journal Ethnic, Racial and Cultural Heritage, 2023)
This study aims to describe the implementation process and symbolic meaning of the ready-to-tek procession carried out by the Dayak Bakati Kanayatn Setango ethnic community. This research uses qualitative research approaches and Victor Turner's interpretation theory, namely Exegetical Meaning, Operational Meaning, and Positional Meaning. The results showed that the ready-to-tek procession consisted of six stages, namely Pamuka Acare, Mileh Badan Siap, Suap Kasih, Nyarah Mahung, Mingkat Patuah, and Panutup Acare. In the procession, there are traditional devices that are used and have important meanings, such as Patunde, Siap Tetek, Pangkuman, Lamang ge Tumpi, and Pangiak Adat. Researchers suggest the need for documentation and more holistic and in-depth research in the field of Sociology related to ethnicity and culture. In addition, the younger generation of the Dayak Bakati Kanayatn Setango ethnic community really needs to learn about local customs and culture so that they can preserve and understand the importance contained in these customs and cultures.